Styryl and phenylethynyl based coumarin chromophores for dye sensitized solar cells - Martins, Sérgio (2018)
A set of coumarin dyes with styryl and phenylethynyl π-bridge at the 3-position were tested for dye-sensitized solar cells (DSSCs). The natural product 6,7-dihydroxycoumarin (Esculetin) was used as starting material. Crucial steps for extension of the conjugated system involved Sonogashira and regioselective Heck arylation reactions, yielding highly fluorescent molecules. The photophysical characterization showed that the extension of conjugation via the alkynyl bridge resulted in redshifted absorption and emission spectra relatively to the parent compound. Electrochemical studies revealed that this derivatization resulted in a marked decrease in HOMO energy levels, which had a marked effect on sensitized solar cell performance. The overall conversion efficiency of the phenylethynyl derivatives proved to be significantly superior (ca. 45%) to the vinyl derivatives, with 6a showing a 2% conversion.